Purification, crystallization and preliminary X-ray crystallographic analysis of the lumenal domain of the ER-vesicle protein Erv41p from Saccharomyces cerevisiae - Biterova, Ekaterina I. (International Union of Crystallography, 2013)

(untitled)
The membrane protein Erv41p is a major component of COPII-coated vesicles and is thought to play a role in the early secretory pathway in eukaryotic cells. In this study, the full lumenal domain of Erv41p from Saccharomyces cerevisiae (ScErv41p_LD) was recombinantly expressed in Sf9 insect cells and purified by nickel-affinity, ion-exchange and size-exclusion chromatography. ScErv41p_LD crystals were obtained using the sitting-drop vapour-diffusion method and native X-ray diffraction data were collected to 2.0 Å resolution. The crystals belonged to space group P2(1), with unit-cell parameters a = 49.8, b = 76.9, c = 65.1 Å, α = γ = 90.0, β = 104.8°.